2022
DOI: 10.1093/plcell/koac151
|View full text |Cite
|
Sign up to set email alerts
|

KIL1 terminates fertility in maize by controlling silk senescence

Abstract: Plant flowers have a functional life span during which pollination and fertilization occur to ensure seed and fruit development. Once flower senescence is initiated, the potential to set seed or fruit is irrevocably lost. In maize, silk strands are the elongated floral stigmas that emerge from the husk-enveloped inflorescence to intercept airborne pollen. Here we show that KIRA1-LIKE1 (KIL1), an ortholog of the Arabidopsis NAC (NAM (NO APICAL MERISTEM), ATAF1/2 (Arabidopsis thaliana Activation Factor1 and 2) a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 48 publications
0
14
0
Order By: Relevance
“…In the Japanese morning glory ( Ipomoea nil ), InEPH1 is regulated by the ethylene pathway factor InEIN2 through an unknown molecular mechanism and regulates downstream PCD genes involved in accelerated flower senescence (Shibuya et al ., 2014). In maize, KIL1, an ortholog of the Arabidopsis NAC TF KIRA1, accelerates the senescence of maize filaments through PCD to terminate flower pollination (Šim Škov et al ., 2022). In tulips, the overexpression of TgNAP accelerates petal senescence, whereas silencing TgNAP delays senescence.…”
Section: Diversity Of Regulation Function Of Nac Tfsmentioning
confidence: 99%
“…In the Japanese morning glory ( Ipomoea nil ), InEPH1 is regulated by the ethylene pathway factor InEIN2 through an unknown molecular mechanism and regulates downstream PCD genes involved in accelerated flower senescence (Shibuya et al ., 2014). In maize, KIL1, an ortholog of the Arabidopsis NAC TF KIRA1, accelerates the senescence of maize filaments through PCD to terminate flower pollination (Šim Škov et al ., 2022). In tulips, the overexpression of TgNAP accelerates petal senescence, whereas silencing TgNAP delays senescence.…”
Section: Diversity Of Regulation Function Of Nac Tfsmentioning
confidence: 99%
“…Previous studies have reported that maize silks undergo an accelerated process of senescence in response to compatible pollination (Bassetti and Westgate 1993; Sella Kapu and Cosgrove 2010; Šimášková, et al 2022). Thus, we searched for senescence-associated genes within the differentially expressed genes in maize silks as a result of compatible pollination.…”
Section: Resultsmentioning
confidence: 99%
“…Despite the conserved overall patterns, we identified differences in the duration of the growth, peak and deterioration phases in the three wheat MS cultivars used here. Gene expression studies of unpollinated carpels and stigma in Arabidopsis and maize ( Carbonell-Bejerano et al, 2010 ; Gao et al, 2018 ; Šimášková et al, 2022 ) have demonstrated that the lifespans of these floral structures are controlled by transcription factors that regulate developmental programmed cell death in these tissues. Here, we also identified distinct waves of expression of genes encoding senescence-associated TFs across late stigma development in a single wheat MS cultivar.…”
Section: Discussionmentioning
confidence: 99%